Reducing waiting times of elective surgical procedures: effectiveness evaluation of a multi-interventions approach - Quercioli, C.; Cevenini, G.; Messina, G.; Carta, G. A.; Becattini, G.; Sancasciani, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Increasing waiting times for elective surgery is a major concern for policymakers and healthcare staff in many countries, due to its effect on health, patient satisfaction and the perceived quality of healthcare. Many organizational models to reduce surgical waiting times have been studied, but the international literature indicates that multidimensional interventions on different aspects of the surgical pathway can be more effective in reducing waiting times than interventions focused on optimizing a single aspect.Aim. The aim of the study is to evaluate the effectiveness of a multidimensional intervention in reducing waiting times for elective surgery.Study design. We used a pre-post approach to evaluate the effect of a multidimensional project to reduce waiting times and lists.Methods. In a district general hospital (Italy) with three elective surgery operating rooms open 6 hours/ day, 5 days/week (surgery specialties: general surgery, orthopaedics, gynaecology and urology), a project for reducing surgery waiting times was implemented in October 2018. The project focused on three aspects: • i) separation of the flow of day surgery from that of ordinary surgery; ii) increasing available operating time by reorganizing the staff; iii) allocation of operating sessions flexibly in proportion to the waiting list. Waiting times for surgery in the periods 1/10/2019-31/12/2019 and 1/10/2018-31/12/2018 were compared by t test.Results. Waiting times for non-high-priority cases shortened significantly for all specialities (p